Lazer e empresa: uma análise da percepção de associados da GREMIG que trabalham na CEMIG - EDUARDO PENNA DE SA (2020)
The aim of this research is analyzing the perception of workers from a large company in Minas Gerais (CEMIG), members of its recreational association (GREMIG), about spaces and leisure activities offered, identifying the limits and the possibilities of these actions and the use of spaces by workers. The methodology was based on a descriptive-quantitative study. Since it is considered only one company, the case study was chosen as one of the research methods, also using the Survey method, gathering the information, thru a semi-closed online questionnaire. The results showed that leisure offered by the company is considered as an option for workers, for whom leisure is related to quality of life, fun, searching for satisfaction, resting and breaking routine. Leisure is most experienced on weekends and in different spaces, and the pool is the most sought after. The main leisure activities attended are the parties of celebrations and the June party. The reasons for seeking leisure programs are due to quality of life and social interaction. Workers recognize that the greatest benefits for the company are the corporate image improvement and the work environment. Distance from home and lack of time are the main limitations for participation. Some workers have an opinion on developing programs but there is no formal evaluation. Then, it is concluded that the worker realizes the leisure offered as part of his/her routine and even though it is offered by the company / association, it is considered as a personal choice. However, this could be more complete, including the assumption of the effective right to leisure taking into account the free choices of the workers groups of the company / association.